Advances in understanding the role of inflammatory factors and immune cells in the pathology of epilepsy, mediated by neuroimmune interactions within the gut-brain axis - Zhang, Lijia; Xu, Rongjiang; Huang, Hao; Yang, Juan; Yu, Changyin; Zhang, Haiqing; Xu, Zucai (Frontiers in Cell and Developmental Biology, 2025)
Epilepsy is a prevalent chronic neurological disorder, affecting approximately 70 million individuals globally, with its pathogenesis primarily attributed to recurrent seizures caused by abnormal neuronal discharges in the brain. Recent research has increasingly recognized the critical role of neuroinflammation in the central nervous system in the onset and progression of epilepsy. Furthermore, the gut-brain axis, a crucial link between gut microbiota and the central nervous system, facilitates communication through intricate pathways involving neural, immune, and endocrine mechanisms, and its involvement in epilepsy pathology is gaining significant attention. This review focuses on recent advances in neuroimmune interactions within the gut-brain axis in epilepsy. It explores the roles of inflammatory factors (e.g., IL-1β, IL-6, TNF-α) and immune cells (e.g., microglia, macrophages, neutrophils) in epileptic pathophysiology, and systematically reviews relevant experimental and clinical studies. The article begins by providing an overview of the fundamental interactions between gut microbiota and the host immune system, before discussing how gut-derived immune signals influence the central nervous system via the gut-brain axis. The pathogenic mechanisms of key pro-inflammatory factors in epileptogenesis are then examined, including how IL-1β promotes neuronal hyperexcitability, how IL-6 mediates neuroinflammation, and how TNF-α disrupts the balance between neuronal excitation and inhibition. Additionally, the article highlights the significant role of inflammatory cells in the central nervous system, particularly the activation of microglia and the infiltration of peripheral immune cells in epilepsy development. In conclusion, further investigation into the mechanisms of neuroimmune interactions in the gut-brain axis may lead to the identification of novel biomarkers and therapeutic targets for epileptogenesis, offering new insights and directions for the treatment of refractory epilepsy.